The impacts of liberalization and trade facilitation on economic performance, poverty and income inequality: An analytical study - Sukoco Sukoco; Djoni Hartono; Arianto Patunru (Universitas Islam Indonesia, 2020)
This study examines the impacts of import duty and trade transaction cost reductions on economic performance, poverty, and income distribution inequality, through the top-down computable general equilibrium approach. Findings/Originality: It reveals that reducing import duty in agricultural decreases urban poverty but increases the poverty incidence at the rural and national levels. Reducing import duty in agricultural industry lowers urban and national poverty without affecting rural poverty. Meanwhile, the reductions of both import duty and transaction costs bring down the poverty incidence at all levels – urban, rural, and national. The inequality in rural and national income distribution increased due to the cuttings of import duty in agricultural and agricultural industry. However, it declined due to the reduction of transaction costs, and the combined transaction cost with import duty in agricultural or agricultural industry.